Pterostilbene ameliorates insulin sensitivity, glycemic control and oxidative stress in fructose-fed diabetic rats - Kosuru R.; Singh S. (My University, 2025)
Aims The present investigation was designed to explore the effectiveness of pterostilbene (PT) on insulin resistance, metabolic syndrome and oxidative stress in fructose-fed insulin resistant rats. Main methods Age-matched, male Sprague-Dawley rats (330 ± 30 g body weight) were allocated into five groups (n = 10). Control (C) group received 65% cornstarch, and the diabetic (D) group received 65% fructose for eight weeks. The third group (D + PT20) received 65% fructose and PT 20 mg/kg/day for eight weeks. The fourth group (D + PT40) received 65% fructose and PT 40 mg/kg/day for eight weeks. The fifth group (D + M) received 65% fructose and metformin (M) 100 mg/kg/day for eight weeks. PT was dissolved in 10% β-cyclodextrin and given orally to rats. Several biochemical parameters were determined to assess the PT efficacy against insulin resistance, metabolic complications, and hepatic oxidative stress. Key findings Significantly high HOMA-IR (p < 0.001) values in D group compared to C group indicate the presence of insulin resistance. Significantly high levels of TBARS (p < 0.001) and decreased levels of SOD (p < 0.001) and GSH (p < 0.001) in hepatic tissues of D group indicate oxidative stress associated with insulin resistance. Pterostilbene treatment to fructose-fed diabetic rats significantly decreased HOMA-IR (p < 0.001) values. Furthermore, PT treatment significantly decreased hepatic TBARS (p < 0.001) and increased SOD (p < 0.001) and GSH (p < 0.001) levels in fructose-fed diabetic rats. Significance Current study reveals that PT is successful in ameliorating glycemic control, insulin sensitivity while diminishing metabolic disturbances and hepatic oxidative stress in a fructose-induced T2DM rat model. © 2017 Elsevier Inc.